2019
DOI: 10.2147/ppa.s189345
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors associated with the doctor–patient relationship: doctor and patient perspectives in hospital outpatient clinics of Inner Mongolia Autonomous Region, China</p>

Abstract: Purpose The doctor–patient relationship (DPR) in People’s Republic of China is very tense. This study aimed to provide some explanation by exploring factors influencing the DPR from doctors’ and patients’ perspectives. Methods A cross-sectional study was conducted in one provincial and one city-level general public hospital in Inner Mongolia Autonomous Region of People’s Republic of China. The Difficult Doctor–Patient Relationship Questionnaire (DDPRQ-10) and the Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 19 publications
3
24
1
14
Order By: Relevance
“…Although these senior doctors had rich experience in communication with patients, their workload and work pressure affected the doctor-patient relationship. In addition to the above factors, substantial previous studies have suggested that doctors with high income satisfaction could maintain a harmonious relationship with patients [30,37,38,54]. In Germany, America, and Italy, a better health workers-patient relationship was correlated with higher job satisfaction [68][69][70], which was con rmed by many previous studies [14,[71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although these senior doctors had rich experience in communication with patients, their workload and work pressure affected the doctor-patient relationship. In addition to the above factors, substantial previous studies have suggested that doctors with high income satisfaction could maintain a harmonious relationship with patients [30,37,38,54]. In Germany, America, and Italy, a better health workers-patient relationship was correlated with higher job satisfaction [68][69][70], which was con rmed by many previous studies [14,[71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have explored the effects of various factors on the HWPR, such as health worker-related factors (i.e., age [13][14][15][16][17][18][19], gender [19][20][21][22][23][24][25], years of experience [26,27], education level [28][29][30], ethnicity [30], marital status [29], professional title [31,32], department [13,33,34], income [30,35,36], income satisfaction [30,37,38], etc. ), patient-related factors (i.e., age [29,30,36], gender [29,30,36], residence [39][40][41], ethnicity [30], education level [42,43], medical insurance [32,44], medical expense [44], household income [30], waiting time...…”
Section: Introductionmentioning
confidence: 99%
“…Although these senior doctors had rich experience in communication with patients, their workload and work pressure affected the doctor-patient relationship. In addition to the above factors, substantial previous studies have suggested that doctors with high income-satisfaction could maintain a harmonious relationship with patients [ 45 , 52 , 53 , 73 ]. In Germany, America, and Italy, a better healthcare workers-patient relationship was correlated with higher job satisfaction [ 100 , 101 , 102 ], which was confirmed by many previous studies [ 29 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to analyze the determinants of the TR and to establish effective strategies to improve such relationships. Previous studies have explored the effects of various factors on the TR, such as healthcare worker-related factors (i.e., age [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ], gender [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ], years of experience [ 41 , 42 ], education level [ 43 , 44 , 45 ], ethnicity [ 45 ], marital status [ 44 ], professional title [ 46 , 47 ], department [ 28 , 48 , 49 ], income [ 45 , 50 , 51 ], income satisfaction [ 45 , 52 , 53 ], etc.,), patient-related factors (i.e., age [ 44 , 45 , 51 ], gender [ 44 , 45 , 51 ], residence [ 54 , 55 , 56 ], ethnicity [ 45 ], education level [ 57 , 58 ], medical insurance [ 47 , 59 ], medical expense [ 59 ], household income [ 45 ], waiting time [ 45 ], etc.,), and other factors (i.e., doctor-patient trust [ 60 …”
Section: Introductionmentioning
confidence: 99%
“…However, some patients with the cN0 lateral neck might need secondary operations due to positive nodes in lateral compartments during surveillance. Because of the current harsh medical environment in China [19] , suspicious metastatic LNLNs are found via color Doppler US examinations during the follow-up period after the first operation (subsequent years). On the one hand, a second surgery may be needed.…”
Section: Discussionmentioning
confidence: 99%